Effects of Current Provisional Restoration Materials on the Viability of Fibroblasts - Ulker, Mustafa; Ulker, H. Esra; Zortuk, Mustafa; Bulbul, Mehmet; Tuncdemir, Ali Riza; Bilgin, M. Selim (European Journal of Dentistry, 2009)
Objectives: The aim of the present study was to evaluate the cytotoxic effects of three different provisional restoration materials on fibroblasts. Two bis-acrylic based [Tempofit Duomix (Detax), Protemp 3 Garant (3M ESPE)] and one urethan dimethacrylate [Revotek LC (GC Corporation)] based provisional restoration materials used.Methods: Materials were prepared according to the manufacturers’ instructions in standard teflon disks (2×5mm) and four samples were extracted in 7 ml of Basal Medium Eagle with 10% new born calf serum and 100 mg/ml penicillin/streptomycin for 24 hours. The L929 fibroblast cells were plate (25.000 cells/ml) in well plates, and maintained in a CO2 incubator at 37°C for 24h. After 24 hours, the incubation medium was replaced by the immersed medium in which the samples were stored and the L929 fibroblasts were incubated in contact with eluates for 24 hours at 37°C for 24h. The fibroblast cell viability was analyzed by measuring the mitochondrial activity with the methyltetrazolium test (MTT). Twelve well used for each specimen and experiment repeated for two times. The data was statistically analyzed by Mann-Whitney U tests.Results: The results showed that, Revotek LC and Protemp 3 Garant were not cytotoxic for fibroblast cells when compared to control group (P>.05). However, Tempofit duomix was cytotoxic for L929 fibroblasts when compared to control group and other tested materials (P%.05).Conclusions: Taking into consideration the limitations of an in vitro study, our study indicate that provisional restoration materials might have cytotoxic effects on fibroblasts and should be selected carefully for clinical applications. (Eur J Dent 2009;3:114-119)
Keywords: Provisional restoration materials; Cytotoxicity; Fibroblast; MTT